Parents’ Role: How Full-Time Workers’ Parents Manage Early Childhood’s Screen Time - Septyana Lestari, Cindy; Aris Rahmadani, Ni Kadek (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The high intensity of gadget use among early childhood affects children's social, emotional, and motor physical interactions, causing children to be less active and reducing their interaction with the environment. This is influenced by parents who are busy working, resulting in less monitoring of their children's screen time. This study aims to analyze how full-time working parents manage the screen time of early childhood children. The research uses a qualitative approach with descriptive and case study methods. Data were collected through observation, interviews, and documentation involving 12 parents who have children aged 3-8 years participating in this study. The collected data were analyzed using data triangulation. The results show that parents have tried to manage gadget usage time by setting limits and filtering content suitable for children. However, parents do not fully understand the concept of effective screen time management, as well as the importance of supervision and accompaniment in gadget use. The implications of this study emphasize the importance of education and support for parents to effectively manage their children's screen time to minimize the negative impacts of gadget use on early childhood development.